Analisis Kebutuhan Pengembangan E-Modul Berbasis REACT dalam Pembelajaran Fisika - Nida Nabilla; Sarah Azizah Zahrotunisa; Diah Mulhayatiah; Herni Yuniarti Suhendi (JPPS (Jurnal Penelitian Pendidikan Sains), 2021)
The research aims to analyze the need for developing REACT-based e-modules in learning Physics. The type of research conducted is descriptive research. The subjects of this research were senior high school students. The research instrument was in the form of filling out a questionnaire filled out by students. Needs analysis is carried out to determine the learning resources used by students, obstacles during learning, and learning resources needed by students. The needs analysis results show that 75% of students have learning resource books for learning physics, but 64% of simple harmonic motion materials in learning resource books are challenging to understand. So that 72% of students need teaching materials containing concepts related to everyday phenomena. And 74% of students agree that physics teachers develop e-modules to support physics learning. The student's critical thinking skills obtained 51.8%, including the poor category. It can be concluded that students need learning resources in the form of REACT-based e-modules to improve students' critical thinking skills in Simple Harmonic Motion material.